2023
DOI: 10.1093/plcell/koad228
|View full text |Cite
|
Sign up to set email alerts
|

MYB24 orchestrates terpene and flavonol metabolism as light responses to anthocyanin depletion in variegated grape berries

Chen Zhang,
Zhanwu Dai,
Thilia Ferrier
et al.

Abstract: Variegation is a rare type of mosaicism not fully studied in plants, especially fruits. We examined red and white sections of grape (Vitis vinifera cv. ‘Béquignol’) variegated berries and found that accumulation of products from branches of the phenylpropanoid and isoprenoid pathways showed an opposite tendency. Light-responsive flavonol and monoterpene levels increased in anthocyanin-depleted areas in correlation with increasing MYB24 expression. Cistrome analysis suggested that MYB24 binds to the promoters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 113 publications
0
1
0
Order By: Relevance
“…Sunlight upregulates the expression of crucial genes ( VvDXS and VvTPS ) and transcription factors ( VvMYB24 ) involved in the biosynthesis of grape terpenes, resulting in increased terpene concentrations [ 2 , 24 , 25 ]. A numbers of studies have indicated that LR treatment has a greater effect on glycosylated terpenes than free terpenes [ 11 , 15 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sunlight upregulates the expression of crucial genes ( VvDXS and VvTPS ) and transcription factors ( VvMYB24 ) involved in the biosynthesis of grape terpenes, resulting in increased terpene concentrations [ 2 , 24 , 25 ]. A numbers of studies have indicated that LR treatment has a greater effect on glycosylated terpenes than free terpenes [ 11 , 15 , 26 ].…”
Section: Resultsmentioning
confidence: 99%